Addressing the Marion County Health Department's Need for A Comprehensive Resource Detailing Florida Medicare's Medical Necessity Policies - Ines G. Alamo; Diane M. Harrell (University of North Florida, 2005)
In the face of rising health care costs, the Marion County Health Department (MCHD) and similar organizations must be reimbursed for their services to the public. If health care providers are to be compensated properly, physicians and other practitioners who order tests and procedures must be aware of Medicare policies regarding medical necessity. The project's goal was to create a user-friendly handbook describing medical necessity for commonly ordered tests (Medical Necessity Handbook). MCHD staff members were trained in the use of the handbook and examined it for a two-week period before offering recommendations through unit supervisors. The handbook provides a simple, yet comprehensive resource for finding reimbursable policies so the MCHD can serve the community without sacrificing large financial outputs. Furthermore, the handbook can be easily updated so that it can continue to be useful to the MCHD and other sites that may choose to use it. A flow-chart of instructions for finding policy through the Florida Medicare website was added to handbooks for participants, allowing the Medical Necessity Handbook to continue to be a handy resource for at the MCHD and elsewhere. Use of the handbook is expected to have a positive impact, allowing public provider organizations like the MCHD to run more efficiently and cost effectively.